O mercado educacional superior em Sergipe : efeitos da reatividade causados pelo Enade quanto indicador de qualidade - Caetano, Andrews Veikman Nunes (2019)
The use of indicators has become a strong tool for the formulation of public policies, this assertion is supported by the trust and easy understanding that the numbers can bring. Faced with this phenomenon in the social field, there are researches that raise important questions, we highlight the one about the role played by the indexes and how people react to them and modify their way of thinking and acting. We have developed the study of such phenomena in the narrower educational field, by choosing two higher education institutions, we propose to debate and reflect on the comprehensiveness of the effects of reactivity and self-fulfilling prophecy in a more limited field. The study focuses on the two main universities in the State of Sergipe, the application of questionnaires with questions about the ENADE (National Student Performance Exam), revealing the relationships between the indicator, students and society as a whole. The result will confirm or not the existence of these phenomena, even if it replicates in a more limited field.